Synthetic Small-Molecule Ligands Targeted to Adenosine Receptors: Is There Potential Towards Ischemic Heart Disease? - Qi Xu; Yaw Nana Opoku; Kalwant S. Authi; Agostino Cilibrizzi (Cells)
Ischemic heart disease (IHD) represents a leading cause of global morbidity and mortality. Despite significant advances in treatment achieved over recent decades, as well as various therapeutic strategies available to manage IHD progression currently, the global incidence of this disorder remains high. This review examines essential cell biology aspects of adenosine receptors (ARs), along with the effects of known synthetic small-molecule AR ligands, to provide an up-to-date view on the therapeutic potential towards IHD treatment. In particular, we report here advancements made on a selection of AR synthetic ligands that have demonstrated efficacy in pre-clinical or clinical studies, thereby holding promise as new therapeutic candidates in the field of IHD. Although this work adds further evidence that clinically valid small-molecule therapeutic agents targeting ARs exist, their use represents an emerging area, with most drug prototypes still in the pre-clinical developmental stage and many lacking large-scale clinical trials. The future lies in identifying improved AR synthetic ligands with enhanced efficacy and selectivity, as well as reduced adverse side effects, along with establishing a platform of specific and diversified pre-clinical tests, to inform in turn the resulting clinical investigations.